Prioritizing Personality-Based Pathways of Stress Reactivity and Psychosomatic Illness - Ghasemzadeh, Azizreza; Saadat , Maryam (Journal of Personality and Psychosomatic Research (JPPR), 2026)
This study aimed to identify, conceptualize, and prioritize the personality-based pathways that contribute to stress reactivity and psychosomatic illness through an integrated mixed-method approach. The research employed a two-phase sequential mixed-method design. In the qualitative phase, a comprehensive literature review was conducted until theoretical saturation was achieved, and the extracted data were analyzed using NVivo 14 to identify recurring personality-based mechanisms underlying psychosomatic illness. In the quantitative phase, a structured questionnaire developed from the qualitative findings was distributed to 250 adult participants in the United Arab Emirates. Respondents rated the importance of nine personality-based pathways on a five-point Likert scale. Data were analyzed using SPSS-26, employing descriptive and inferential statistics to rank the identified pathways based on mean scores and standard deviations. The analysis revealed that neuroticism and emotional instability (M = 4.62, SD = 0.41), psychophysiological integration pathways (M = 4.56, SD = 0.48), and alexithymia and emotional unawareness (M = 4.47, SD = 0.53) were the top-ranked predictors of psychosomatic vulnerability. Mid-level contributors included perfectionism and self-criticism, stress appraisal and cognitive schemas, and emotion regulation strategies, while extraversion and social connectivity and conscientiousness and coping regulation ranked lowest, indicating a primarily protective rather than causative role. Inferential tests confirmed significant differences in perceived importance across demographic groups (p < .05), reinforcing the robustness of the model. The findings demonstrate that psychosomatic illness arises from a hierarchical interaction of personality-driven emotional, cognitive, and physiological processes, with neuroticism, alexithymia, and physiological dysregulation forming the core vulnerability triad. These results underscore the importance of personality assessment in psychosomatic health management and highlight the need for personality-informed preventive and therapeutic interventions.